Character formation 2: leadership, decision making, management and administration. - Garcia, mario A. (Philippines; Wisemans Books Trading, Inc., 2022)
This book contains Understanding Self-Leadership -- Organizational Leadership -- Understanding Management -- Decision Making -- Understanding Administration.
Includes Bibliographical references.
English Text
Keywords: Decision making Leadership Administrative leadership